The Echiura of Japan: diversity, classification, phylogeny, and their associated fauna - Goto, Ryutaro (In Motokawa, M., Kajihara, H. (eds). Species Diversity of Animals in Japan, 2017)
Echiurans (spoon worms) are marine invertebrates that have a sausage-shaped unsegmented body with an extensible spoon-like proboscis. Most species live inside burrows in soft sediments. They have been classified as a separate phylum, but recent molecular phylogenetic and phylogenomic studies have consistently suggested that they are derived annelids that lost segmentation. This chapter introduces the classification and phylogeny of echiurans and provides a checklist of echiurans and their symbiotic animals in Japan. Echiurans have traditionally been grouped into three orders: Echiuroinea (with Echiuridae, Thalassematidae, and Bonelliidae), Xenopneusta (with Urechidae), and Heteromyota (with Ikedidae). Recent molecular phylogenetic analyses recover only two groups that contain sexually monomorphic (Echiuridae, Urechidae, and Thalassematidae) and sexually dimorphic species (Bonelliidae and Ikedidae), respectively. The echiuran fauna of Japan comprises 5 families, 19 genera, and 34 species, including 5 thalassematid species newly reported herein. The family Thalassematidae contains 20 species in 6 genera; Bonelliidae contains 10 species in 9 genera; Urechidae and Echiuridae are represented by a single species each (Urechis unicinctus and Echiurus echiurus, respectively); and Ikedidae contains 2 species, (I. taenioides and Ikeda sp. 1). One genus (Acanthohamingia) and 11 described species are known only from Japan. At least 29 commensal species have been collected from 12 species of host echiurans in Japan, including bivalves (7 species), gastropods (3 species), snapping shrimps (4 species), crabs (5 species), polychaetes (mainly scale worms) (7 species), and copepods (1 species). In addition, unidentified entoprocts are also found from thalassematid burrows.
World Polychaeta Database (WPolyDb). Online 01 December 2016, print date 2017